Determinants of consumer perceived trustworthiness in digital advertising of food and beverage - Kesavan Nallaluthan (Tanjong Malim, 2021)
Determinants of consumer perceived trustworthiness in digital advertising of food and beverage by Kesavan Nallaluthan